V-OG03 Robotic Epiphrenic Diverticulectomy, Myotomy And Hiatus Hernia Repair. (16th December 2021) - Knight, Benjamin
Abstract: Background: Oesophageal epiphrenic diverticulum's are rare; reported in less than 0.5 per cent of the population. They are noted however in 1–3 per cent of patients complaining of dysphagia. They are almost always associated with a motility disorder of the oesophagus. Surgery is generally the only solution to help with the symptoms of dysphagia and reflux. Methods: This video highlights a case of a moderate sized diverticulum causing dysphagia and significant reflux. The procedure was performed on the DaVinci X system; to my knowledge, this is the first time this technique has been performed on the DaVinci X in the UK. A 4 arm technique was used, utilising two right arms and one left. Instruments used were cadiere forceps, hook and sureform stapler. The 12 mm port was docked with arm 3 and sited on the patients left. A stapled diverticulectomy was performed with the Sureform blue cartridge. An endoflex was used to retract the liver. Results: The procedure was successfully performed in 150 minutes and involved resection of the diverticulum, hiatal repair and short myotomy up to the neck of the diverticulum. Conclusion: The robotic platform allows for better visualisation of the hiatal structures and vagal nerves and the enhanced magnification make for a safer myotomy. The articulating instruments permit safer dissection of the diverticulum. A 4 arm technique makes the myotomy easier and safer to perform.